Feasibility of clipped node resections with crystal violet dye in patients who underwent biopsies for metastatic lymph nodes: Targeted axillary dissections in Japan. Issue 1 (2018) - Takemae, Masaru; , Michiko Harao; Hoshi, Nobuo; Inada, Takao; Wada, Masahiro; Ando, Jiro
No abstract available